Gene therapy for adenosine deaminase–deficient severe combined immune deficiency: clinical comparison of retroviral vectors and treatment plans - Candotti, Fabio; Shaw, Kit L.; Muul, Linda; Carbonaro, Denise; Sokolic, Robert; Choi, Christopher; Schurman, Shepherd H.; Garabedian, Elizabeth; Kesserwan, Chimene; Jagadeesh, G. Jayashree; Fu, Pei-Yu; Gschweng, Eric; et al. (Blood, 2012)
We conducted a gene therapy trial in 10 patients with adenosine deaminase (ADA)–deficient severe combined immunodeficiency using 2 slightly different retroviral vectors for the transduction of patients' bone marrow CD34+ cells. Four subjects were treated without pretransplantation cytoreduction and remained on ADA enzyme-replacement therapy (ERT) throughout the procedure. Only transient (months), low-level (< 0.01%) gene marking was observed in PBMCs of 2 older subjects (15 and 20 years of age), whereas some gene marking of PBMC has persisted for the past 9 years in 2 younger subjects (4 and 6 years). Six additional subjects were treated using the same gene transfer protocol, but after withdrawal of ERT and administration of low-dose busulfan (65-90 mg/m2). Three of these remain well, off ERT (5, 4, and 3 years postprocedure), with gene marking in PBMC of 1%-10%, and ADA enzyme expression in PBMC near or in the normal range. Two subjects were restarted on ERT because of poor gene marking and immune recovery, and one had a subsequent allogeneic hematopoietic stem cell transplantation. These studies directly demonstrate the importance of providing nonmyeloablative pretransplantation conditioning to achieve therapeutic benefits with gene therapy for ADA-deficient severe combined immunodeficiency.